River flows as drivers of population distribution and settlement patterns in Bosnia and Herzegovina: a GIS-based analysis - Korjenić, Aida; Sivac, Amina; Avdić, Aida (Journal for Geography, 2024)
This paper analyzes the distribution and size structure of settlements along the primary river courses of Bosnia and Herzegovina, considering both hypsometry and socioeconomic dimensions of space, which contribute to demographic transformations. Using GIS tools, an analysis was conducted on the number of settlements according to hypsometric levels in the river basins of the Black and Adriatic Seas, alongside demographic changes during the latest intercensal period. Spatial analysis methods in GIS enabled the identification of population changes, settlement sizes, and spatial distribution patterns. Analysis of buffer zones within 5 km of river streams reveals a predominant spatial clustering of settlements along these waterways, while a fragmentation of settlement networks is observed farther away from the main streams.